Rapid determination of globin chains in red blood cells by capillary electrophoresis using INSTCoated fused-silica capillary - Tůma, Petr (Journal of separation science, 2014)
A laboratory-made INSTCoated fused-silica capillary has been newly used for CE separation of four mixtures of proteins in sodium phosphate BGEs at pH 3.0 and 2.5, respectively. The obtained separation efficiencies range from 145,000 theoretical plates per meter for myoglobin to 1,216,000 m(-1) for lysozyme. A total of 49-89% of the number of theoretical plates was obtained in a commercial polyvinyl alcohol coated capillary compared to the INSTCoated capillary under the same experimental conditions, 0-86% was obtained in a laboratory polyacrylamide-coated capillary, and only 0-6% was obtained in an uncoated fused-silica capillary. The RSD values for the intraday repeatability for an INSTCoated capillary were 0.1-1.0% (migration time) and 0.3-2.4% (peak area); RSD values for the interday repeatability in the same capillary are 0.6-1.4% (migration time) and 2.4-5.5% (peak area); RSD values for interday repeatability between different capillaries equaled 1.7-2.1% (migration time) and 2.8-10.9% (peak area). The INSTCoated capillary has been further used for rapid determination of globin chains isolated from red blood cells. A separation of α and β chains prepared from adult blood has been completed in 3 min with a peak resolution of 1.3, and the separation of α and (G)γ chains prepared from newborn blood took 3 min with a peak resolution of 3.6.
Keywords: Clinical analysis; novorozenec; Infant, Newborn; Humans; Protein separation; globiny; Erythrocytes; Electrophoresis, Capillary; Silicon Dioxide; dospělí; lidé; Globin chains; Globins; elektroforéza kapilární; polymery; Capillary electrophoresis; Adult; Polymers; erytrocyty; oxid křemičitý; Capillary coating